(untitled) (Global Journal of Science Frontier Research, 2022)
Pastoral communities have all along developed local mechanisms for managing forage resources to cope with recurrent severe droughts Unfortunately these practices have been suppressed and communities are struggling from losses succumbed by effects of drought on livestock feeds and water In Kenya pastoral production system supplies the largest percentage of beef to the market as compared to the private sector However the study found out pastoralists have inadequate knowledge and sufficient training on pasture management contributing to low level of pasture conservation during periods of excess pasture The frequently practiced methods were traditional herd tethering and migration A small fraction of pastoralists adopted and practiced modern systems such as Paddocking Zero grazing hay making and use of other supplementary feeds In addition water harvesting technologies to reduce the possibility of rivalry and conflict between and within communities arising from limited water supply during drought should be promoted There is an urgent call for all stakeholders in the pastoral areas of Kajiado East to establish sustainable strategies to accelerate capacity building in pasture resource management